2011
DOI: 10.5137/1019-5149.jtn.5207-11.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effectiveness of facet joint injection and radiofrequency denervation in chronic low back pain

Abstract: AIm:The study was conducted to compare the clinical effectiveness of FJ injections (FJI) and FJ radiofrequency (FJRF) denervation in patients with chronic low back pain. mAterIAl and methOds:This study included 100 patients; 50 in FJI 50 in FJRF group. VNS, NASS and EQ-5D were used to evaluate the outcomes. All outcome assessments were performed at baseline, 3 months, 6 months and 12 months. results: FJI in early post-op but FJRF in 1st, 6th and 12th month VNS showed better results (p<0.001). There was no sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(102 citation statements)
references
References 20 publications
1
93
0
8
Order By: Relevance
“…Celik et al 12 reported a positive effect from FJIs in a subsequent trial (n = 80) comparing FJIs with a combination of bed rest, a non-steroidal anti-inflammatory and a muscle relaxant. In a subsequent trial (n = 100) comparing FJIs with facet joint radiofrequency denervation, Civelek et al 59 found better immediate results from injection and better long-term results from denervation.…”
Section: Facet Joint Injections Compared With Other Treatmentsmentioning
confidence: 99%
“…Celik et al 12 reported a positive effect from FJIs in a subsequent trial (n = 80) comparing FJIs with a combination of bed rest, a non-steroidal anti-inflammatory and a muscle relaxant. In a subsequent trial (n = 100) comparing FJIs with facet joint radiofrequency denervation, Civelek et al 59 found better immediate results from injection and better long-term results from denervation.…”
Section: Facet Joint Injections Compared With Other Treatmentsmentioning
confidence: 99%
“…Civelek et al used the VAS and NASS instrument for pain assessment and EQ‐5D to determine the efficacy of RFT in patients with chronic low back pain. Their results showed notable pain relief after RFT . In clinical practice, however, most patients with chronic pain are elderly and may not understand the items in the questionnaires or do not know how to express their feelings.…”
Section: Discussionmentioning
confidence: 99%
“…Su prevalencia como causa de dolor lumbar está entre el 15-31% 3 con incidencia a lo largo de la vida de hasta el 52% en algunas series [6][7][8][9][10] . Su causa es la degeneración de las articulaciones facetarias, las cuales sufren los cambios propios de cualquier articulación sinovial.…”
Section: Resumen El Dolor Lumbar Es Una Entidad Común Y Frecuente Crunclassified
“…Hay menos evidencias de la utilidad de las terapias conservadoras en su manejo, las cuales únicamente parecen tener utilidad como terapias adyuvantes [15][16] . Actualmente el abordaje estándar de tratamiento consiste en bloqueos nerviosos y rizolisis o neurolisis de la rama medial del ramo dorsal del nervio espinal [8][9][10][11][12][13][14] .…”
Section: Resumen El Dolor Lumbar Es Una Entidad Común Y Frecuente Crunclassified